The Ecological Crisis and the Reformed Theology of Creation: An Analysis - Robin, Lope B. (Silliman Journal, 2022)
This paper examines the Reformed Theology of Creation as espoused by one of the leading protestant reformers John Calvin. For Calvin, creation primarily serves as a means of God’s revelation. That is, through creation the human being obtains knowledge of God and experience the goodness of God. This is so because the world of nature discloses the majesty, power, and the graciousness of God. Moreover, Calvin underscores that God nourishes and sustains both the human and nonhuman creatures through creation. In this sense, Calvin’s position suggests the upholding of the integrity and well-being of creation for it to continue to serve its intended purpose as willed by God. As such, Calvin has a strong contention that God cares for all creatures. However, he failed to emphasize human responsibility towards the world of nature in ensuring that creation will continue to serve its purpose as originally intended by God.